Overview of Pharmacy Service Standards In 3 Pharmacies In Sumber District - Fauziah, Salsa Syifa; Hidayat, M. Taufik; Ma'arif, Syamsul; Rosdaniati (Jurnal Ilmu Kesehatan (JIKSAN), 2025)
Pharmaceutical Service Standards in Pharmacies are the basis for service as a benchmark used as a guide for pharmaceutical personnel in providing pharmaceutical services. This study aims to describe the implementation of Pharmaceutical Service Standards in Pharmacy based on the Regulation of the Minister of Health Number 73 of 2016 in 3 Pharmacies in Sumber District. This type of research is descriptive qualitative with data collection using a questionnaire. The research results showed that the implementation of pharmaceutical services in 3 pharmacies in Sumber District was in accordance with Minister of Health Regulation No. 73 of 2016 is 100% for pharmaceutical preparation management and 99% for clinical pharmacy services. Service standards that have not been implemented in all pharmacies, namely Drug Therapy Monitoring (PTO) and Drug Side Effect Monitoring, Counseling Room Infrastructure Facilities and Prescription Reception Rooms.